SISTEM PERINGATAN DINI DAN PENENTU TINGKAT BAHAYA KEBAKARAN MENGGUNAKAN MIKROKONTROLLER ATMEGA 16 - Paronda, Abdul Hafid; Marini, Sri; Hidayat, Nurul (JREC (Journal of Electrical and Electronics), 2013)
This thesis describes the design of an early warning system against fire, the overall systemconsists of hardware and software. The hardware system consists of temperature sensors and gas sensorsthat detect signs of fire the detection of gas, smoke and increase in temperature in a room. All detectedinformation is processed by a microcontroller atmega16 that function ring alarm form buzzer, exos fanand hydrant based on predefined parameters, namely â¤ 36 Â° for safe levels indicated green, â¥46Â° forstandby levels indicated yellow, â¥60Â° for alert levels indicated red and last â¥80Â° for evacuation levelsindicated red and to transmit the data to the server computer via serial communication lines. BorlandDelphi7 as software (user interface) on a computer server function display and record the results of thetwo sensor readings along with the details of time, date, month and year.Keyword : Early Warning Fire, Serial Communications, User Interface, ATMega16, Delphi7.